Aspects of physical training related with upper respiratory tract infections: a review - Ahmadi, Shirko; Brietzke, Cayque; Silveira, Rodrigo; Prado, Raul Cosme Ramos do; Brietzke, Ricardo; Aguiar, Samuel da Silva; Asano, Ricardo Yukio; Coelho-Júnior, Hélio José (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
The upper respiratory tract infections (URTI) are characterized by symptoms present, mainly, in the nose and pharynx. Physical exercise is one of the factors that can lead to development of URTI, causing a state of immunosuppression during a small-time interval, making the athlete susceptible to development of acute infectious states. Besides its influence in athlete’s quality of life and healthy, the progression of URTI seems to be associated with overtraining state, inducing reduction on physical performance. Several authors have been discussing how the variables of exercise training can alter the incidence and prevalence of URTI, and the present study was developed to present the current knowledge about this tissue, discussing how the modulation in the exercise training variables may interfere in the URTI. Methods: This is a review study. Results: Athletes with different levels of training and different categories in most diverse modalities seem to suffer from symptoms of URTI in training and competitive periods. Increasing of URTI symptoms seems to be related to internal training load and evidence has pointed out that suppression of serum and salivary immunoglobulin concentrations appear to be a factor which influences appearance of these symptoms and may even be used as markers of immune status of athlete. Conclusion: In point of view of reviewed articles, athletes with different levels of training and different categories in most diverse modalities seem to suffer from symptoms of URTI in training and competitive periods. Increasing of URTI symptoms seems to be related to internal training load and evidence has pointed out that suppression of serum and salivary immunoglobulin concentrations appear to be a factor which influences appearance of these symptoms and may even be used as markers of immune status of athlete. However, studies that verify and provide “cutoff points” that indicate a higher risk for URTI onset is still needed.